STRATEGI PENGEMBANGAN MODEL PEMASARAN BERAS ORGANIK BERBASIS CONSUMER’S MARKET DI KABUPATEN BANYUMAS - Hartati, Amy; Putri, Dindy Darmawati (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
At  present,  many  farmer  groups  at  Banyumas  Regency  are  cultivating organic  rice.  Their  activities  are  very  progressive.  They  distribute  at  Baturraden, Sumbang,  Kedungbanteng,  and  Pekuncen.  The  activities  are  closed  relation  in  the market.  There  is  trend  in  moving  from  seller’s  merket  to  consumer’s  market.  The market  is  not  determined  by  middle  trader,  but  end  product   consumer  (consumers driven).  In  the  case,  consumer’s  require  complete  information  about  physical, chemical  and  biological  characters  of  product.  Therefore,  producers  must  enclose liable information on labels. The goals of  research were to analyze farming activity of organic rice, and study on consume’s preferences. Survey method was used, followed descriptive-qualitative analysis, and principal component analysis (PCA) for finding out  factors  affecting  consumers  in  buying  organic  rice  and  consuming  the  products based on profile and character of consumers. The research showed that (1) organic rice  cultivation  was  profitable;  (2)  Attributes  of  organic  rice  consisting  of  price,flavor,  availability,  and  guarantee  of  product  are  important;  (3)  Consumers  are satisfied to the organic rice producer’s perfomance in determining price and flavor. We recommend to the producer for maintenance of quality (flavour), availability and guarantee of product.